2022
DOI: 10.1021/acs.iecr.1c04142
|View full text |Cite
|
Sign up to set email alerts
|

Rotten Eggs Revaluated: Ionic Liquids and Deep Eutectic Solvents for Removal and Utilization of Hydrogen Sulfide

Abstract: Hydrogen sulfide (H2S) is highly toxic and one of the problematic impurities in industrial gas streams, calling for H2S removal down to single-digit ppm levels to protect health and environment, and not to harm to the downstream processes. Here, we discuss the recent developments and challenges of current H2S removal technologies. Furthermore, we present a comprehensive review of H2S removal in ionic liquids (ILs), IL-based solvents/adsorbents/membranes, and deep eutectic solvents (DESs) due to their unique ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 205 publications
0
14
0
Order By: Relevance
“…An alternative source of H 2 is hydrogen sulfide, although it is conventionally overlooked. Gaseous H 2 S is recognized for its characteristic rotten egg odor and its health hazards at concentrations as low as 10 ppm (Li et al, 2022). H 2 S is found concurrently in gas and oil reservoirs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative source of H 2 is hydrogen sulfide, although it is conventionally overlooked. Gaseous H 2 S is recognized for its characteristic rotten egg odor and its health hazards at concentrations as low as 10 ppm (Li et al, 2022). H 2 S is found concurrently in gas and oil reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…The last technique is common in current Claus H 2 S treatment units. They are operated above the dew temperature of sulfur (180 °C) to avoid precipitation (Li et al, 2022). However, its implementation becomes more delicate when the purpose of the reaction is to obtain H 2 (Lim and Winnick, 1984;Weaver and Winnick, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…To eliminate acidic gases from natural gas, various procedures are adopted [4]. Ionic liquids (ILs) can be utilized in absorbing environmentally harmful acidic gases [5]. Machine learning can be used to check ILs for gas absorption because they are cost effective and non-toxic in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the deteriorated eggs contain some amounts of H 2 S gas produced by bacteria degrading various sulfides and emitting awful rotten egg odors. 10 Furthermore, H 2 S is also considered one of the key indices of red wine quality, and inferior wines usually contained higher concentrations of H 2 S. 11−13 The aromatic flavor of the wine is related to the generated aroma components by the strong redox effect of the wine itself. 14 When the concentration of H 2 S is over 1.1 μg/L, it would has an adverse effect on the flavor and quality of the wine.…”
Section: Introductionmentioning
confidence: 99%
“…As a kind of reactive sulfur species (RSS) material and an essential thiol-containing molecule, H 2 S plays multifunctional roles in resisting oxidative stress and sustaining the normal physiological function of organisms including neurotransmission, vasodilation, insulin secretion, apoptosis, and inflammation. , In addition, the aberrant fluctuation of H 2 S levels was found to be attributed to a series of illness, such as pathobolism, neurological degenerative diseases, diabetes, Alzheimer’s disease cardiovascular diseases, cancers, and inflammations. , Moreover, it has been confirmed that hydrogen sulfide existed in many foodstuffs and industry wastewater naturally. The drained H 2 S-containing wastewater can pollute seriously the water environment and foodstuffs and induce severe damage to human health. Generally, the deteriorated eggs contain some amounts of H 2 S gas produced by bacteria degrading various sulfides and emitting awful rotten egg odors . Furthermore, H 2 S is also considered one of the key indices of red wine quality, and inferior wines usually contained higher concentrations of H 2 S. The aromatic flavor of the wine is related to the generated aroma components by the strong redox effect of the wine itself .…”
Section: Introductionmentioning
confidence: 99%